Post placental copper-T 380A insertion after normal vaginal delivery and cesarean section and its clinical outcome - Malik, Jyoti; Das, Ashima; Rai, Pinki; Das, Sibadatta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post placental IUCD insertion refers to the insertion of IUD within 10 minutes of expulsion of placenta. Intra-cesarean section is insertion of IUD after removal of placenta before closure of uterine incision. The objective of this study was to study the efficacy, safety and effect on menstrual cycle, expulsion, continuation and failure rate of post-placental copper-T 380A after vaginal and cesarean birth over the period of 1 year in tertiary centre. Methods: A total 150 women who opted for insertion of copper-T 380A within 10 minutes of expulsion of placenta whether delivered vaginally or by cesarean section, were enrolled in study. Women having past history of ectopic pregnancy or any genital tract infection or hemorrhagic disorders, uterine anomaly, chorioamnionitis, LPV>18 hours, unresolved PPH, Hb<8 g% were excluded from the study. Results: No incidence of perforation, PID or failure of contraception was detected. Percentage of satisfaction among users after 6 weeks 91%, 3 months 92.9% and 6 months 95.6%. Conclusions: Although there was high incidence of missing IUCD threads (due to coiling of thread), actual expulsion rate was far lesser. Removal rate due to menorrhagia, pain abdomen and vaginal discharge was low and 6 months continuation rate was considerably good.